A transfer weighted extreme learning machine for imbalanced classification. Issue 10 (2nd May 2022) - Guo, Yinan; Jiao, Botao; Tan, Ying; Zhang, Pei; Tang, Fengzhen
Abstract: Previous class imbalance learning methods are mostly grounded on the assumption that all training data have been labeled, however, is impractical in many real‐world applications. The limited amount of labeled instances may produce a classifier with poor generalization. To address the issue, a transfer weighted extreme learning machine (TWELM) classifier is proposed, with the purpose of extracting knowledge from other domains to improve the classification performance of a classifier in a limited labeled target domain. To be specific, a well‐tuned weighted extreme learning machine classifier is first learned from source data that has been completely labeled. Subsequently, another extreme learning machine classifier is obtained from the limited labeled target domain data to preserve the target domain structural knowledge and the decision boundary information. Finally, the target classifier is optimized by minimizing the outputs of the two classifiers on unlabeled target data. Experimental results on real‐world data sets show that TWELM outperforms existing algorithms on classification accuracy and computation cost.